Antitrust Private Enforcement and the Binding Effect of Public Enforcement Decisions - Miguel Sousa Ferro (Market and Competition Law Review)
This paper provides an overview of the legal status quo in the European Union relating to the binding effect, in follow-on competition law cases, of public enforcement decisions, as well as of some of the legal issues which are likely to be the subject of controversy in years to come, in this regard. It tackles decisions declaring antitrust infringements adopted by the European Commission and by national competition authorities, as well as commitment decisions and decisions declaring infringements of merger control and State aid rules. It discusses the material, subjective and temporal scope of the binding effect. It also tackles other issues, such as the obligations of national courts relating to non-infringement decisions and ongoing investigations, and the issue of negative declarations. Finally, it looks into the arguments which may be put forward by litigants before national courts to avoid or circumvent the binding effect of public enforcement decisions. It is argued that the case-law already provides answers to many of the issues which are likely to be raised, which one may arrive at through a systematic and coherent interpretation of the general principles of EU Law, as clarified by the Court.